The hydraulics of open channel flow : an introduction ; basic principles, sediment motion, hydraulic modelling, design of hydraulic structures /: an introduction ; basic principles, sediment motion, hydraulic modelling, design of hydraulic structures. (2004) - Unknown
No abstract available